What is the reason for out-toeing gait on the injured side after surgical treatment of distal tibia physeal fractures? - Giray Batibay, Sefa; Turkmen, Ismail; Erkan Yenigul, Ali; Saglam, Yavuz (Annals of Medical Research, 2021)
Aim: The aim of this study was to analyze the cause of out-toeing gait pattern in children who underwent anatomic reduction and internal fixation for distal tibial physeal injury. Material and Methods: This IRB-approved, Level IV review study included traumatic distal tibia epiphyseal injury treated surgically at a single institution between 2010 and 2015. Patients were called back to return for additional follow-up. All clinical (foot progression angle-FPA, hip rotations, thigh foot angle-TFA) and radiological (distal tibial measurements) evaluations were done by 2 independent observers to assess inter- and intra-observer reliability using intraclass correlation coefficients (ICC). Results: There were 38 patients with an average age of 11.4±3.8. There was a non-significant trend noted towards externally in FPA on the injured side. TFA was similar in both extremities (p: 0.56). Hip external rotation was significantly high in injured side, whereas hip internal rotation was similar. Hip external rotation was significantly high.Conclusion: Anatomic joint reduction is mandatory to prevent growth arrest and to maintain lower extremity alignment. Considering that there is no pathology of the hip and no radiologic signs of mal-alignment of the ankle, we think that hip external rotators may shortened due to post-operative resting position, which was ended up with out-toeing gait pattern on the injured side.
Keywords: Ankle fracture; out-toeing; pediatric fractures; physeal fractures